2016
DOI: 10.1007/s10943-016-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

“Wake Up! HIV is at Your Door”: African American Faith Leaders in the Rural South and HIV Perceptions: A Qualitative Analysis

Abstract: In Alabama, 70 % of new HIV cases are among African Americans. Because the Black Church plays an important role for many African Americans in the south, we conducted qualitative interviews with 10 African American pastors recruited for an HIV intervention study in rural Alabama. Two main themes emerged: (1) HIV stigma is prevalent and (2) the role of the Black Church in addressing HIV in the African American community. Our data suggest that pastors in rural Alabama are willing to be engaged in HIV prevention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…A particularly noteworthy finding is the disconnection between pastors' and church leaders' views of HIV associated risk. Previous literature has indicated that most pastors perceive their congregations as being at lower or no risk for HIV [23][24][25]. In contrast, the pastors in this sample reported that there was a high likelihood that members of their congregation, particularly young boys and men, were engaging in risk behaviors that may put them at risk for HIV.…”
Section: Discussioncontrasting
confidence: 64%
“…A particularly noteworthy finding is the disconnection between pastors' and church leaders' views of HIV associated risk. Previous literature has indicated that most pastors perceive their congregations as being at lower or no risk for HIV [23][24][25]. In contrast, the pastors in this sample reported that there was a high likelihood that members of their congregation, particularly young boys and men, were engaging in risk behaviors that may put them at risk for HIV.…”
Section: Discussioncontrasting
confidence: 64%
“…Faith communities have been intending and engaging in HIV preventive solutions, training to decrease stigma, and strengthen support for PLHIV (Aholou et al, 2016). There is a need to develop a therapy module that integrates spirituality, mental health, and biopsychological models (Amjad & Bokharey, 2015).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…We learned from the pastors that HIV stigma was prevalent, but the pastors believed that Black Churches have an important role to play in addressing HIV in the African American community. A more detailed account of the qualitative findings from the interviews is provided elsewhere (Aholou et al, 2016). Pastors also provided demographic information about their congregation and any HIV prevention activities conducted at their churches.…”
Section: Phase 1: Assessmentmentioning
confidence: 99%